The Kids and Teens at School (KiTeS) Framework: An Inclusive Bioecological Systems Approach to Understanding School Absenteeism and School Attendance Problems - Melvin, Glenn A.; Heyne, David; Gray, Kylie M.; Hastings, Richard P.; Totsika, Vaso; Tonge, Bruce J.; Freeman, Mina Mirjana (Frontiers in Education, 2019)
Absence from school jeopardizes children's and adolescents' education and their social and emotional development. Proximal and distal individual, parental, familial, and environmental factors have been linked to absenteeism and the development and maintenance of school attendance problems. The complex interaction among these factors necessitates a multifactorial approach to understanding school absenteeism and attendance problems. The current paper builds on recent calls to apply bioecological systems frameworks when studying risk factors for school absenteeism and attendance problems. The Kids and Teens at School (KiTeS) Framework presented here is an application of Bronfenbrenner's bioecological systems model, incorporating candidate factors of particular relevance to school absenteeism and attendance problems. The current paper is also a response to the Warnock report which highlighted the need to individualize educational supports for children and adolescents with disabilities, to foster optimal educational outcomes. The KiTeS Framework is an inclusive framework, inclusive of students with and without disabilities. It is envisaged that the KiTeS Framework will provide guidance to researchers aiming to improve understanding of the factors influencing absenteeism among all school-aged students, including those from minority or vulnerable populations.